Venom of the Peruvian snake Bothriopsis oligolepis: Detection of antibacterial activity and involvement of proteolytic enzymes and C-type lectins in growth inhibition of Staphylococcus aureus. (August 2017) - Sulca, M.A.; Remuzgo, C.; Cárdenas, J.; Kiyota, S.; Cheng, E.; Bemquerer, M.P.; Machini, M.T.
Abstract: There is a rising interest in snake venoms proteins (SVPs) because these macromolecules are related to pharmacological properties that manifest themselves during poisoning and can lead to secondary microbial infections. Interestingly, researchers have somehow neglected the antimicrobial activity of SVPs. The aims of this study were: (i) to verify whether the venom of the Peruvian snake Bothriopsis oligolepis displays such activity; (ii) to isolate and identify some of its antimicrobial constituents. Liquid growth inhibition assays revealed that the crude venom inhibited the growth of Gram-positive and Gram-negative bacteria, but not of Candida species. Fractionation of the venom by anion-exchange chromatography provided fractions P2, P4 and P8 active against S. aureus . Fractionation of P2 or P8 by gel-filtration chromatography and of P4 by RP-HPLC furnished the sub-fractions P2-I, P8-II and P4-II, respectively, being those fractions active against S. aureus . Analyses of these sub-fractions by SDS-PAGE under denaturing/reducing conditions evidenced SVPs with 59–73, 27 and 14–28 kDa, respectively. Their in-gel tryptic digestion gave peptide fragments, whose sequencing by MALDI-TOF/MS followed by protein BLAST analysis allowed identifying PIII metalloprotease(s) [SVMP(s)] in P2-I, serine protease(s) [SVSP(s)] in P4-II and lectin(s) in P8-II. Detection of gelatinolytic activity in P2-I and P4-II reinforced the existence of PIII-SVMP(s) and SVSP(s), respectively. Activation of the coagulation cascade intrinsic pathway by P8-II (probably by interaction with factors IX and/or X as some snake C-type lectins do) supported the presence of C-type lectin(s). Altogether, these new findings reveal that the venom of the Peruvian snake Bothriopsis oligolepis displays antibacterial activity and that the isolated SVMP(s), SVSP(s) and C-type lectin(s) are associated to its ability to inhibit the growth of S. aureus . Graphical abstract: Highlights: We first observed bacterial activity of the Peruvian snake B. oligolepis crude venom. SVMP, SVSP and C-type lectins are related to the venom's activity against S. aureus . This is the first report on SVSP involvement in such venom's property.